Importance of Spirit of Inquiry in Engineering Education - Sunil Cavale, S.; Bharadwaj, Vibhu A.; Shashi Kiran, B. N.; Murthy, Madhav (Journal of Engineering Education Transformations, 2016)
This work is a study into the necessity of scientific temperament in engineers. It aims at the study of general trends in engineering education through time, from the point of view of scientific spirit-curiosity, experimentation, repeatability and precision. Here, an undergraduate degree comprising both science and engineering is proposed, and the same is examined from various perspectives, which are arrived at on the basis of statistical evidence. The study conducted (survey) clearly establishes the need to bridge science and engineering. The survey was based on four criteria - performing experiments, student bodies (technical clubs), external sources for learning, and pure science subjects taught in engineering. More than 60% of the survey-takers, i.e. students, converged on the need for an undergraduate degree comprising science and engineering. Some important specifications of such a degree, shaped from the survey, are as follows: Its duration can be about four years; research and skill development should be its primary focus; all engineering institutions have to offer it.